Crude Drug Standardization, Formula Optimization, and Interaction Effects of a Five-Component Antioxidant Polyherbal Formulation - Wardani, Tri Kusuma; Arianingsih, Elfa; Syarifah, Arini; Hamad, Alwani; Hartanti, Dwi (Tropical Biopharmaca Research Center, IPB University, 2025)
A polyherbal formulation was developed from java tea (Orthosiphon aristatus (Blume) Miq.), turmeric (Curcuma longa L.), seed-under-leaf (Phyllanthus niruri L.), cinnamon (Cinnamomum verum J. Presl), and ginger (Zingiber officinale Roscoe). This study aimed to standardize crude drugs, optimize polyherbal formulations, and evaluate the interaction effect of the crude drug mixture. Standardization followed these methods and compared them with the Indonesian Herbal Pharmacopeia (IHP) standards. The crude drugs were mixed in 26 different ratios, and each formulation was extracted using the decoction method. The antioxidant activities of the extracts were evaluated using 2-diphenyl-2-picryl hydroxyl scavenging (DPPH) radical scavenging activity and ferric-reducing antioxidant power (FRAP) assays. The optimum formula was obtained by antioxidant activity-based prediction using the simplex lattice design (SLD) method. The interaction effects of crude drug mixtures were determined using a statistical comparison method for the predicted and obtained antioxidant activities. Crude java tea, turmeric, cinnamon, and ginger were of good quality. The five-component formulation with optimum antioxidant activity consisted of java tea, turmeric, seed-under-leaf, cinnamon, and ginger crude drugs in a ratio of 20-20-40-10-10 with interaction effects of additive toward DPPH radical scavenging activity (7.05±0.94 µmol TE/g) and antagonistic toward FRAP (19.37±0.94 µmol TE/g). Formula 21 (mixture of java tea and seed-under-leaf crude drugs) showed the highest DPPH scavenging activity (6.39±0.16 µmol TE/g) with synergistic effects, while the synergistic, highest FRAP (23.74±0.03 µmol TE/g) was shown by Formula 13 (mixture of seed-under-leaf and ginger crude drugs).